Sauropod and theropod dinosaur tracks from the Upper Cretaceous ofMendoza (Argentina): Trackmakers and anatomical evidences - Gonzalez Riga, Bernardo Javier (2015)
New findings of dinosaur ichnites from Agua del Choique section (Mendoza Province, Argentina) provides ichnological and anatomical information about the Cretaceous sauropods and theropods. Around 330 tracks distributed in six footprint levels were identified in this area, one of most important of South America. Two ichnocenoses are located in different paleoenvironmental contexts. In the Anacleto Formation (early Campanian) around 20 titanosaurian tracks were found in floodplain and ephemeral channel deposits. Herein, one pes track shows three claw impressions and this is congruent to two new titanosaur specimens recently discovered in Mendoza Province that have articulated and complete pedes. In this context, for the first time to titanosaurs, ichnological evidences are supported by skeletal elements. In the Loncoche Formation (late Campanian-early Maastrichtian) titanosaurian tracks of Titanopodus mendozensis are abundant (around 310 tracks) and were produced by titanosaurs that walked in a very wet substrate of tidally dominated deltas related with the first Atlantic transgression for northern Patagonia. In this facies association, three different trydactl tracks indicate the presence of small theropods (1-2m long), expanding the knowledge about the faunistic components that lived in these marine marginal environments.